KAJIAN HIDROGRAF SATUAN SINTETIK NAKAYASU UNTUK PERHITUNGAN DEBIT BANJIR RANCANGAN DI DAERAH ALIRAN SUNGAI KODINA - Sutapa, I Wayan (MEKTEK, 2005)
Analyse of the design discharge in the catchment area can be used by some methods, one of them is Synthetic Unit Hydrograph Nakayasu. In this method applying need presumably studied so that result got well enough. The Synthetic Unit Hydrograph Nakayasu try applied in catchment area Kodina in Central Sulawesi to look for the level of deviation of Synthetic Unit Hydrograp Nakayasu with the measured unit hydrograph. Modification of Equation of Synthetic Unit Hydrograph Nakayasu conducted by degrading basic formula the time peak (Tp) from value Tr and peak discharge (Qp) from equation T03 in the form of value α (discharge coefficient). As the result of research show happened by the big enough deviation to nature of the basic unit hydrograph of namely for the Tp = 26% and Qp = 22,40%. So,  Synthetic Unit Hydrograph  Nakayasu cannot be used direct to calculate the design discharge in catchment area Kodina. It’s required research of a kind to Synthetic Unit Hydrograp Nakayasu to look for the coefficient  from value of Tp and Qp